Moving the Theory of Parental Cooperation and Innovation into Practice - Westergard, Elsa (International Journal about Parents in Education, 2023)
Although many schools and teachers are aware the important factors for effective parental cooperation, they seem to lack an understanding of how to transform this theoretical knowledge into practice. One reason for this difficulty appears to be that teachers have traditionally focused more on what is needed to practice good cooperation with parents and less on how they can implement this knowledge in practice. The aim of this paper is to reveal how research-based knowledge within parental cooperation (what) and implementation (how) can contribute to developing teachers’ individual competence into schools’ collective competence within “challenging conversations with parents”. Taking a systems approach, we see that what is happening within the two separate systems—family and school—affects cooperation between the two parties. Thus, there is a need for a holistic view on cooperation. We draw upon recent research, qualitative and quantitative, on parent collaboration, revealing the important factors behind successful cooperation between parents and teachers. Our research suggests that teachers and schools need more individual and collective competence when working with parents. More specifically, teachers need additional competence and strategies when engaging in challenging conversations with parents. Transforming research-based knowledge about parental cooperation into practice is not a mechanical operation. We need different types of knowledge and approaches to implement strategies for teachers to handle challenging conversations with parents. This paper presents some strategies to help teachers accomplish this.